Efficacy of Metronidazole in Combination with Amoxicillin and Doxycycline in Adult Periodontitis - Sarah Moideen; Rafeeq Alam Khan; Afaq Ahmed Siddiqui (Journal of Basic & Applied Sciences, 2013)
Objective:Periodontal diseases are amongst most prevalent diseases in the world. They are caused by poor oral hygiene, accumulation of dental plaque and virulent putative pathogens on the teeth and gums Systemic antibiotics are used as adjuncts for the treatment of this infective disease. The objective of this study was to compare the efficacy of two antibiotic drug combinations i.e., Metronidazole with Amoxicillin and Metronidazole with Doxycycline in patients with adult periodontitis. Method:50 patients were divided in two groups. They were given fixed doses for 7 days to patients with Adult Periodontitis. Readings were taken before treatment and two weeks prior to the treatment. The result was evaluated on the basis of periodontal Pocket depth, Bleeding Index and Mobility Index. The readings were taken using Periodontal Probe, dental Mirror and dental Explorer. Result: There was significant reduction (p<0.01) observed in periodontal pocket depth and Bleeding Index incase of Doxycycline, Metronidazole combination in comparison to Amoxicillin, Metronidazole combination. There was slight change observed on Mobility Index. Conclusion: The study suggested that Doxycycline and Metronidazole should be preferably given for Adult Periodontitis.